Analysis of Entropy Generation in a Generalized Couette Flow between Two Concentric Pipes with Buoyancy Effect - A. S. Eegunjobi; O. D. Makinde; A. P. Oluwagunwa (Journal of Advanced Thermal Science Research, 2016)
Heat transfer and entropy generation analysis in buoyancy driven generalized Couette flow of variable viscosity fluid within the annulus of two concentric cylindrical pipes are theoretically investigated. It is assumed that the inner cylinder is fixed while the outer one is subjected to axial motion. The governing nonlinear equation models are obtained and solved numerically using shooting quadrature. The results for velocity and temperature profiles are utilized to compute entropy generation number and the Bejan number. Relevant results are displayed graphically and discussed quantitatively.